Intensive (P-T-fO2) crystallization parameters of Alto Paranaíba kimberlites and diamond instability: Três Ranchos IV and Limeira I intrusions - Coldebella, Bruna (2019)
Temperature (T), Pressure (P) and Oxygen fugacity (fO2) conditions were established for the Três Ranchos IV (diamond-bearing) and Limeira I (sterile) kimberlites of the Coromandel-Três Ranchos kimberlite field (Minas Gerais and Goiás, Brazil), Alto Paranaíba Alkaline Province (APAP), in order to draw a possible correlation between these intensive crystallization parameters and diamond instability. Both Três Ranchos IV and Limeira I are classified as coherent macrocrystic kimberlites, with an inequigranular texture formed by partially-to-fully altered olivine, phlogopite megacrysts up to 1 cm wide, macrocrysts (0.5-10 mm-sized), and crustal xenoliths set in a very fine groundmass composed mainly by perovskite, olivine, phlogopite, spinel, serpentine and carbonates identified in both intrusions. Apatite, ilmenite and monticellite are also present, but only in LM-I. Garnet macrocrysts and centimetric pyroxene xenocrysts phases are also present in Três Ranchos IV and Limeira I, respectively. The samples, strongly enriched in incompatible elements, are all MgO-rich, with high Mg# content. In order to apply different geotherm-and-oxybarometers in the calculation of P-T-fO2 conditions and to characterize the compositional variation of TR-IV and LM-I kimberlites, major, minor and trace-element concentrations of the main mineral phases were obtained by electron microprobe and LA-ICP-MS. Olivine cores of Limeira I present higher NiO, CaO and lower Cr2O3 contents than those from Três Ranchos IV. Mg# [(Mg/Mg+FeT), mol.%) ranges from 87 to 92 mol.% in TR-IV and from 83 to 92 mol.% in LM-I. The trace-element contents of olivine are similar in both kimberlites, the concentrations of Li, Zn and Mn appearing to be higher at olivine rims. In olivines from both intrusions, a pattern of enrichment in Zr, Ga, Nb, Sc, V, P, Al, Ti, Cr, Ca, and Mn in rims regions, is observed in the \"melt trend\" whereas enrichment in Zn, Co, Ni and possibly Na in cores regions, is found in the \"mantle trend.\" In monticellite specimens from Limeira I, Mg# ranges from 72 to 93.8, while Ca/(Ca+Mg) ratios range from 35 to 58 mol.%. The perovskite composition in both LM-I and TR-IV remains close to the ideal CaTiO3, perovskite, but a variation from core endmembers (average Lop16 and Prv78) towards the rims (average Lop13 and Prv81) can be noticed in TR-IV samples. The highest concentrations of light rare earth elements (LREE), Nb, and Fe3+ are also observed in perovskites from the TR-IV kimberlite. Macrocrystic spinels of TR-IV kimberlite are Al-rich, whereas the groundmass crystals range from magnesiochromite to chromite. Ilmenites from LM-I are characterized by high MgO values at a given TiO2, with a large variation in Cr2O3. Pyrope garnets (62 to 73 mol.%) are present only in TR-IV, with Mg# ranging from 72 to 79 mol.%, being classified as lherzolitic (G9) and pyroxenitic (G4, G5). Diopside occurs as xenocrysts in LM-I and as microphenocrysts in TR-IV, with Mg# ranging from 85 to 91 and from 87 to 92, respectively. Xenocrystic diopsides from LM-I present higher MgO and FeO concentrations with monticellite grains along crystal rims and fractures. Temperature estimates for the LM-I kimberlite, obtained from the composition of diopside xenocrysts and Al-in olivine concentrations, ranging from 718 to 985 °C. Pressure ranges from 34 to 47 Kbar, as calculated using an empirical curve from a 37-mW/m2 geotherm proposed in the literature for Alto Paranaíba magmas. For TR-IV, temperature values ranging from 975 to 1270°C were obtained from Al-in olivine and Ni-in garnet concentrations. Pressures in the range from 18 to 34 Kbar were obtained from major element composition of garnet samples from TR-IV kimberlite. The fO2 of the TR-IV constrained by perovskite (kimberlite cognate phase) oxygen barometry ranges from NNO-7 to NNO+4, while for LM-I values range from NNO+6 to NNO-4. For the LM-I intrusion, monticellite, another cognate phase used as an oxybarometer, yielded a value range of NNO-4 to NNO+2. A change in the oxygen fugacity from cores towards rim recorded in the perovskites and the monticellite crystals is also noticed. The oxygen fugacity estimates of this work are the first ever calculated for magmas of the Alto Paranaíba Alkaline Province. All P-T-fO2 values obtained are consistent with literature data on the APAP. Clinopyroxene xenocrysts from LM-I were classified as garnet-facies clinopyroxene, according to the compositions obtained in this work. Such results, along with pressure, and temperature data from and the presence of Mg-ilmenite in LM-I (known to be sterile), indicate that the kimberlite magma might have at least crossed the diamond stability field. The variation in oxygen fugacity observed in both kimberlites possibly reflects the instability of diamonds in these magmas since LM-I presents slightly higher oxidation conditions.